Effectiveness of enhanced recovery after surgery with whey protein - infused carbohydrate loading on postoperative outcomes among gynaecologic cancer patients - Ho, Chiou Yi (2020)
Background: Enhanced Recovery after Surgery (ERAS) with preoperative sole carbohydrate (CHO) loading is widely proven in reducing the length of postoperative hospital stay (LPOHS) without increasing complications among gastrointestinal and gynaecologic cancer (GC) patients. However, ERAS with preoperative whey protein-infused CHO loading among GC patients is unexplored. This randomised controlled trial aimed to determine the effectiveness of ERAS with preoperative whey protein-infused CHO loading on postoperative outcomes among GC patients. Method: The trial recruited 62 subjects as intervention group (CHO-P), who received preoperative whey protein-infused CHO loading and 56 subjects as control group (CO), which were given conventional care. Postoperative outcomes including surgical outcomes, postoperative complications, nutritional (body composition, dietary intake and biochemical profile) and functional status (handgrip strength) were studied. Body composition involved in this study were muscle mass, fat percentage, fat-free mass and fat mass, while biochemical profile assessed were full blood count, albumin and C-reactive protein. Body composition was measured via TANITA body composition analyser, nutritional status via PG-SGA, dietary intake via 24- hour diet recall, handgrip strength via Jammar Dynamometer. Pearson Chisquare, paired t-test, independent t-test and two-way mixed model ANOVA were used to analyse the data. One-way ANCOVA was used to detect for any covariates. Result: The mean age for CHO-P was 49.5 ± 12.2 years and CO was 51.2 ± 11.9 years. Majority of the subjects were Malay (70%), followed by Chinese (19%) and India (11%). Subjects’ diagnosis distribution was 42% ovarian cancer, 34% endometrial cancer, 18% cervical cancer and 6% uterine cancer. Total energy intake of subjects was 1385 ± 327 kcal/day, while total protein intake was 56.7 ± 16.6 g/day. Percentage weight loss within 1 month were -4.5 ± 6.8% and -5.3 ± 7.2% for CHO-P and CO, while PG-SGA scores were 6.7 ± 5.2 and 7.0 ± 5.5, respectively. CHO-P showed significantly positive results in the trial, which included shorter LPOHS (78.13 ± 33.05 hours vs. 99.49 ± 22.54 hours, p<0.01), less postoperative nausea and vomiting (17% vs 24%, p<0.01), a lower readmission rate within one-month postoperative (6% vs. 16%, p<0.05), lower weight loss (−0.3 ± 2.3 kg vs. −2.1 ± 2.3 kg, p<0.01), lower Creactive protein–albumin ratio (0.3 ± 1.2 vs. 1.1 ± 2.6, p<0.05), more preserved muscle mass (0.4 ± 1.7 kg vs. −0.7 ± 2.6 kg, p<0.01), and better handgrip strength (0.6 ± 4.3 kg vs. −1.9 ± 4.7 kg, p<0.01) as compared with CO. However, there were no significant differences in mid-upper arm circumference and serum albumin level upon discharge. Discussion and conclusion: ERAS with preoperative whey protein-infused CHO loading not only assured better surgical outcomes without increasing postoperative complications and readmission rate, but also achieved a superior preservation of nutritional status and muscle strength, as well as suppression of postoperative acute phase inflammatory marker among GC patients. This approach with a multidisciplinary involvement and collaboration is recommended to be integrated into routine perioperative nutritional intervention management in surgical oncology to ensure better postoperative outcomes.